Silver-based nanocomposite materials for marine antifouling applications - Yee, Swee Li Maxine (2018)
Biofouling of marine surfaces is an age-old problem that affects natural and man-made surfaces exposed to the aquatic environment. The tenacious attachment of seaweed and invertebrates to man-made surfaces, notably on ship hulls, has incurred undesirable economic losses. The initial stage of the biofouling process has been attributed to the attachment of marine bacteria and their subsequent formation of biofilm which attract the settlement of larger sessile organisms including barnacles and seaweed.